A second chance after incarceration : the public attitudes towards former inmates returning to work - Sigurlaug Sara Gylfadóttir 1995- (2020)
The purpose of this study was to examine attitude towards former inmates from the public in Iceland, not many studies that have examined this topic in Iceland. Participants in this study were 311 individuals from the general public, 200 females (64.3%) and 111 males (35,7%). The questioner that was used was a translated version of an Attitude towards crime scale (ACS). The questioner was divided into two sections, hereditary and individual causes and social and environmental causes. The results of the study showed that 96.5% (n=300) of the general public where positive in regards to inmates returning to the labor market after incarceration and be given a second chance. The results also showed that there is not a positive correlation between having a personal relationship with a former inmate and being in favor of them returning to work. Participants with a high education level are more positive when it comes to former inmates returning to work. And finally, there is not a significant statistical difference between genders when it comes to attitude towards former inmates. It would be of interest to do a more detailed study on this topic and gather data from former inmates themselves to see what kind of attitude they face when returning to work and if they do indeed get a second chance Keywords: Attitude, former inmates, labor market Tilgangur rannsóknarinnar var að skoða viðhorf almennings gagnvart fyrrum afbrotamönnum á Íslandi, en ekki hafa verið gerðar margar rannsóknir hér á landi varðandi þetta viðfangsefni. Þátttakendur rannsóknarinnar voru 311 talsins, 200 konur (64.3%) og 111 karlar (35.7%). Notast var við þýddan spurningakvarða sem kannar viðhorf fólks til glæpa (ACS), spurningarnar skiptust upp í tvo hluta, arfgengar og einstakar ástæður og félagslegar og umhverfislegar ástæður. Niðurstöður rannsóknarinnar sýndu fram á að 96.5% (n=300) þátttakenda töldu að fyrrum afbrotamenn eigi skilið annað tækifæri á vinnumarkaði eftir afplánun. Niðurstöðurnar sýndu að það er ekki martækur munur á milli þess að ...